Scrotal Calcinosis: an Idiopathic Entity? - Bollea Garlatti, María Rocío; Di Prinzio, Anamá; Ferrario, Damián; Staiger, Hernán; Mazzuoccolo, Luis D. (Revista del Hospital Italiano de Buenos Aires, 2023)
Scrotal calcinosis is a benign and infrequent disease that presents in middle-aged adults with multiple asymptomatic nodules on the scrotal skin. Some authors link the appearance of these lesions to secondary calcification of epidermal or eccrine cysts. When not due to these entities or alterations of phosphocalcic metabolism, they become idiopathic. The treatment of choice is surgery in case of impact on the patient’s quality of life or aesthetic relevance.